Sikap masyarakat terhadap pengembangan Pantai Loang Baloq sebagai daya tarik wisata di Kota Mataram - M. Setyo Nugroho (Journal of Enterprise and Development (JED), 2019)
Purpose — This study aims to determine the community's attitude towards the development of Loang Baloq Beach in Mataram City.Research method — Data were collected using observation techniques to Loang Baloq Beach, documentation studies in the form of documents related to Loang Baloq Beach, and distributing questionnaires to 100 people (accidental sampling) around Loang Baloq Beach, Mataram City.Result — The result showed that the community agrees with the development of Loang Baloq Beach in the hope that it can become an economic locomotive and a place to promote Loang Baloq Beach at the international level. However, there are still some people who do not agree with the development of Loang Baloq Beach. This is because they think that tourism brings more harm than benefits.